On Transmission System Design for Wireless Broadcasting - Himmanen, Heidi (Turku Centre for Computer Science, 2009)
This thesis considers aspects related to the design and standardisation of transmission systems for wireless broadcasting, comprising terrestrial and mobile reception. The purpose is to identify which factors influence the technical decisions and what issues could be better considered in the design process in order to assess different use cases, service scenarios and end-user quality. Further, the necessity of cross-layer optimisation for efficient data transmission is emphasised and means to take this into consideration are suggested. The work is mainly related terrestrial and mobile digital video broadcasting systems but many of the findings can be generalised also to other transmission systems and design processes. The work has led to three main conclusions. First, it is discovered that there are no sufficiently accurate error criteria for measuring the subjective perceived audiovisual quality that could be utilised in transmission system design. Means for designing new error criteria for mobile TV (television) services are suggested and similar work related to other services is recommended. Second, it is suggested that in addition to commercial requirements there should be technical requirements setting the frame work for the design process of a new transmission system. The technical requirements should include the assessed reception conditions, technical quality of service and service functionalities. Reception conditions comprise radio channel models, receiver types and antenna types. Technical quality of service consists of bandwidth, timeliness and reliability. Of these, the thesis focuses on radio channel models and errorcriteria (reliability) as two of the most important design challenges and provides means to optimise transmission parameters based on these. Third, the thesis argues that the most favourable development for wireless broadcasting would be a single system suitable for all scenarios of wireless broadcasting. It is claimed that there are no major technical obstacles to achieve this and that the recently published second generation digital terrestrial television broadcasting system provides a good basis. The challenges and opportunities of a universal wireless broadcasting system are discussed mainly from technical but briefly also from commercial and regulatory aspect